ANALISIS KESIAPAN KOMPETENSI GURU PAUD DALAM PEMBELAJARAN BERBASIS DIGITAL: STUDI KASUS DI SATUAN PAUD KOTA PADANG - Audia Fajar, Insanillahia; Octarina , Merlyn; Sundari, Ayu; Eliza, Delfi (STKIP Subang, 2026)
Teacher competence is a determining factor in the success of early childhood education (PAUD). This study aims to analyze the level of teacher competence in PAUD units, including pedagogical, personality, social, and professional competencies. The study used a quantitative descriptive approach with a survey method. The sample consisted of 45 PAUD teachers from 15 PAUD units in Padang City, West Sumatra. Data were collected through questionnaires, observation, and documentation. The results showed that PAUD teachers' pedagogical competence was in the sufficient category (63.4%), personality competence was in the good category (78.2%), social competence was in the good category (74.5%), and professional competence was in the sufficient category (61.8%) in digital-based learning. These findings indicate that there is still a need to systematically improve the pedagogical and professional competence of PAUD teachers, especially in digital-based learning, through training programs, ongoing training, and academic qualification enhancement.